Measurement of turbulent flows with a rotated hot-film anemometer - Peterka, Jon A., author; Marsh, G. Leonard, author; Fluid Mechanics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1977)
Numerous research efforts have been devoted to measuring the velocity characteristics of turbulent flows in order to understand the nature and physical processes of these flows. A new hot-film anemometer technique to measure the mean velocity vector and the six components of Reynolds stress in turbulent flows is discussed in this report. During the development of this measurement system, emphasis was placed on the simplicity in which velocity measurements could be obtained in a three-dimensional turbulent flow and on the accuracy of the acquired data. A Monte Carlo simulation technique was used to predict the resolution in the measurement quantities. Validation experiments were conducted by obtaining turbulent velocity measurements in a fully developed turbulent pipe flow and also in a turbulent shear flow (simulating the planetary boundary layer). Velocity measurements were also obtained in the wake of a power plant model immersed in a turbulent boundary layer to demonstrate the capability of the measurement system. Measurements of the Reynolds stress components in the fully developed turbulent pipe flow showed good agreement with predictions based on the measured pressure drop in the pipe and data taken by other investigators. Reynolds stress measurements taken in the turbulent shear flow also compared well with data taken by other investigators. The scatter in the measurements of the turbulent velocity components indicated that the Monte Carlo method was accurately predicting the resolution in these measurement quantities.
CER76-77GLM-JAP64.
Supported by National Science Foundation Grant.
May 1977.
Keywords: Fluid dynamics; Turbulence -- Measurement